Hyperleukocytosis in infant acute leukemia: a role for manual exchange transfusion for leukoreduction - Runco, Daniel V. (Transfusion, 2018)
BACKGROUND: Hyperleukocytosis is a serious, life-threatening complication of pediatric acute leukemia that can cause neurologic injury, pulmonary leukostasis, metabolic derangements, and coagulopathy. Acute leukemia has the highest risk of mortality and morbidity at presentation when associated with hyperleukocytosis. Infant leukemia presents unique challenges and treatment considerations due to the disease itself and size and overall health of the patient. While medical management of hyperleukocytosis in older patients with acute leukemia has been described, including cytoreductive procedures with automated leukapheresis (AL) or manual whole blood (WB) exchange transfusion, very little data exist for standardized management of hyperleukocytosis in infant leukemia patients. CASE REPORTS: We describe four cases of infant acute leukemia presenting with hyperleukocytosis and leukostasis who each received manual WB exchange transfusions in conjunction with induction chemotherapy and review the existing literature on the use of procedural leukoreduction in infants with hyperleukocytosis. Special attention is given to challenges and technical aspects of leukapheresis in infants: when to perform manual WB exchange versus AL, optimal vascular access, blood product selection, exchange rates, and the monitoring for complications. Using published cases, we outline benefits versus risks of manual WB exchange and AL in infants less than 10 kg. CONCLUSION: If providers perform procedural leukoreduction, the literature and our experience demonstrate manual WB exchange transfusion is favored over AL in infants less than 10 kg because of technical and complication risks associated with AL. Additional studies are needed to understand the impact of cytoreduction on long-term outcomes.